Effectiveness Analysis of Yield Management Implementation in Hotel ABC - Syafruddin, Hasya Millatina (Journal of Business and Management, 2012)
Yield management is a popular application of total revenue maximization tactics in service industry. Hotel ABC located in Bandung already implemented yield management in 2008 but the management never assessed the effectiveness of the implementation. Therefore, the main purpose of this paper is to do assessment of yield management effectiveness in Hotel ABC, using the matrix created by Bernard McEvoy and comparison financial reports. The analysis was done with three methods: demand plotting, Bernard McEvoy’s matrix and comparing financial statements. For a high/low cut off comparison, Horwath HTL had provided the figures of financial excerpt of Bandung hotels in 2008. The outcome of the analysis shows that the demand for superior, deluxe rooms in weak season and executive rooms in peak season are elastic. While for the other rooms, the elasticity didn’t belong to any category. In overall, Hotel ABC’s total revenue had increased significantly and 2008 revenue increase is higher than previous years’ increase. Further analysis shows that Hotel ABC still can gain more revenue from sales room in a significant amount. However, Hotel ABC increased operating expenses, while in the same time other Bandung hotels decreased it. It was found that Employees’ salary was the greatest increase in the operating expenses. Keywords : yield management, hotel industry, operating efficiency, demand plotting